2016
DOI: 10.17816/ecogen1423-18
|View full text |Cite
|
Sign up to set email alerts
|

Genesis of the karelian birch. an ecogenetic hypothesis

Abstract: Relying on the analysis of data from the literature and own findings the authors develop and specify the previously postulated ecological-genetic hypothesis of the curly birch origins, which is based on the concept of interactions between specific natural-climatic factors and conditions in the north-western continental Europe during so-called Little Ice Age (LIA), the high genetic polymorphism, and the adaptive nature of many anatomical-morphological traits and physiological-biochemical characteristics of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…In this study we attempted to unravel the enigma of genetic factors underlying the phenomenon of curly wood in Karelian birch, which has been debated for over a century 32 . Although in 1922 it was already shown that the patterned texture of the wood is quite stably transmitted to progenies during seed propagation 33 , there were many adherents of the ‘infectious’ or ‘pathological’ hypotheses, which considered curly wood to be the result of exposure to biotic or abiotic stressors 34–36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study we attempted to unravel the enigma of genetic factors underlying the phenomenon of curly wood in Karelian birch, which has been debated for over a century 32 . Although in 1922 it was already shown that the patterned texture of the wood is quite stably transmitted to progenies during seed propagation 33 , there were many adherents of the ‘infectious’ or ‘pathological’ hypotheses, which considered curly wood to be the result of exposure to biotic or abiotic stressors 34–36 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study we attempted to unravel the enigma of genetic factors underlying the phenomenon of curly wood in Karelian birch, which has been debated for over a century 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Одним из вопросов, связанных с интенсификацией воспроизводства высокодекоративных по текстуре древесины форм карельской березы, является установление механизмов формирования указанных морфолого-анатомических особенностей. Основываясь на литературных материалах можно выделить ряд основных гипотез происхождения карельской березы, учитывающих экологическую, филогенетическую, биохимическую, физиологическую, фитопатологическую и наследственную специфику данной породы, однако ни одна из предложенных концепций досконально не объясняет возникновение и воспроизведение структурно-функциональных аномалий, а также не находит полного экспериментального подтверждения, что, по всей видимости, указывает на многофакторный характер формирования признака узорчатости древесины [1].…”
unclassified